Dengue-Associated Hemophagocytic Lymphohistiocytosis With Severe Multiorgan Complications—A Case Report. Issue 1 (June 2021) - Agrawal, Rahul; Agrawal, Prabha; Madhuri, Sudha; Singh, Thakur Abhijit
Hemophagocytic lymphohistiocytosis (HLH) is a rare life-threatening syndrome characterized by pathologic immune hyperactivation, extreme inflammation, and multiorgan involvement with variable cytopenias. We report a case of a 53-year-old male with no known comorbidities, who presented with unrelenting dengue fever, pancytopenia, high ferritin levels, and multiple organ dysfunction with progressive clinical deterioration despite treatment. Based on the clinicolaboratory findings, he was diagnosed as dengue-associated HLH on day 6 of admission. As per HLH treatment protocol, he was started on immunosuppressants and showed significant improvement. In dengue patients with severe disease, prolonged hospital stay, persistent cytopenia, and multiorgan dysfunction out of proportion to the plasma leakage phase should prompt a high index of suspicion for the possibility of infection-triggered HLH. Although prompt diagnosis and early initiation of therapy is the key to prevent irreversible end organ damage and mortality, the hindrance lies in its rarity in adults, variable clinical presentation, and nonspecific laboratory findings.